2018
DOI: 10.1002/eap.1805
|View full text |Cite
|
Sign up to set email alerts
|

Ecological change alters the evolutionary response to harvest in a freshwater fish

Abstract: Harvesting can induce rapid evolution in animal populations, yet the role of ecological change in buffering or enhancing that response is poorly understood. Here, we developed an eco‐genetic model to examine how ecological changes brought about by two notorious invasive species, zebra and quagga mussels, influence harvest‐induced evolution and resilience in a freshwater fish. Our study focused on lake whitefish (Coregonus clupeaformis) in the Laurentian Great Lakes, where the species supports valuable commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
(203 reference statements)
0
16
0
Order By: Relevance
“…The latter is well exemplified by human exploitation or purposeful artificial selection in wild or captive populations. Size and age selective fishing induces the evolution of early maturity, slower growth, smaller size [68][69][70]. Early studies in insects showed that directly selecting for further culture, only offspring born to primiparous parents lead to the quick evolution of reduced lifespan [71].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is well exemplified by human exploitation or purposeful artificial selection in wild or captive populations. Size and age selective fishing induces the evolution of early maturity, slower growth, smaller size [68][69][70]. Early studies in insects showed that directly selecting for further culture, only offspring born to primiparous parents lead to the quick evolution of reduced lifespan [71].…”
Section: Discussionmentioning
confidence: 99%
“…Lake whitefish are a commercially harvested fish in the Great Lakes, with Lake Huron contributing the highest catches among the Great Lakes (Brenden et al 2013). In Lake Huron, lake whitefish have undergone changes over time in population abundance, growth, recruitment, and ages and sizes at maturity (Gobin et al 2015(Gobin et al , 2016(Gobin et al , 2018. Lake whitefish ages and sizes at maturation are predicted to evolve in response to harvest, depending on factors such as the minimum size limit and harvest rate (Dunlop et al 2018, Gobin et al 2018.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Changes in maturation traits, generally towards earlier maturation at smaller sizes, have been observed in numerous exploited fish populations (Trippel 1995;Law 2000;Sharpe and Hendry 2009) and have preceded substantial declines in stock productivity (Trippel 1995;Olsen et al 2004). Harvesting can lead to maturation-related change demographically, through the truncation of the age and size distribution of the population (Heino and Dieckmann 2008), through density-dependent phenotypic plasticity (Trippel 1995), and from genetic change brought about by selective harvest (i.e., harvest-or fisheries-induced evolution) (Hutchings and Fraser 2008;Heino et al 2015;Dunlop et al 2018). Rates of change in the timing of maturation of exploited stocks have been rapid (Trippel 1995;Sharpe and Hendry 2009;Devine et al 2012;Audzijonyte et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, eco-genetic models have further revealed that the presence and strength of density-dependent plasticity in somatic growth can alter the amount and direction of direct harvest selection (Gobin et al 2018, Modulation pathway in Fig. 1).…”
Section: /37mentioning
confidence: 99%